2022
DOI: 10.3390/d14100798
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of and Threats to Sicilian Turtles

Abstract: Based on the critical review of the literature published in the last 22 years, an attempt was made to evaluate the current knowledge gap on the distribution and status of the native Testudines taxa occurring in Sicily (namely Caretta caretta, Emys trinacris, and Testudo hermanni hermanni), as well as the available knowledge of the only non-native species with putative viable populations occurring on the island, i.e., Trachemys scripta. Summarizing the current information, all of the Testudines species occurrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 83 publications
(123 reference statements)
0
4
0
Order By: Relevance
“…Currently, CC-A2.1 is the most commonly encountered haplotype, present in more than 60% of the free-living Mediterranean loggerhead sea turtles [21,[56][57][58][59][60]. This haplotype dominates most Mediterranean nests and has been detected in all nesting areas studied [22,41,59,61,62]. Haplotype CC-A3.1 is the second most commonly encountered haplotype in the Mediterranean Sea and accounts for around 20% of the free-living individuals studied [21,[56][57][58].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, CC-A2.1 is the most commonly encountered haplotype, present in more than 60% of the free-living Mediterranean loggerhead sea turtles [21,[56][57][58][59][60]. This haplotype dominates most Mediterranean nests and has been detected in all nesting areas studied [22,41,59,61,62]. Haplotype CC-A3.1 is the second most commonly encountered haplotype in the Mediterranean Sea and accounts for around 20% of the free-living individuals studied [21,[56][57][58].…”
Section: Discussionmentioning
confidence: 99%
“…To the effects of climate change on sea turtle nest success must be added those caused by human activities such as the construction of buildings along the coasts, the construction of ports and/or artificial breakwater barriers, the diversion and/or overbuilding of watercourses (resulting in a reduced input of sediments that reach the sea), and the occurrence of pollutants (e.g., Savoca et al, 2021;Savoca et al, 2022). This description concerns a large portion of the Italian sandy shorelines (Borzì et al, 2021) and has direct implications for Caretta caretta management (Vecchioni et al, 2022a). The loggerhead sea turtle Caretta caretta is the most common and studied species among the sea turtles present in the Mediterranean Sea.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, such information is not very useful as it is often unreliable and lacking essential information. Conversely, scientific papers dealing with this topic appear to date rather limited (e.g., Blasi et al, 2022;Denaro et al, 2022;Vecchioni et al, 2022a;Vecchioni et al, 2022b). Recently, Hochscheid et al (2022) have shown that from 2010 to 2023 in the western sector of the Mediterranean Caretta caretta has shown a progressive expansion of the nesting area, as evidenced by the occurrence of a high number of nests in areas where the females had never been known to lay eggs before.…”
Section: Introductionmentioning
confidence: 99%
“…LIUZZO et al [2020] reported the sighting of a female T. scripta laying eggs in Lago di Pergusa (Sicily, Italy). Besides that, nothing is known about its possible reproduction success and establishment of self-sustaining populations in Sicily, and information on the distribution of the species on the island is scant [BELLA, TURRISI 2005;LILLO 2008;VECCHIONI et al 2022].…”
Section: Introductionmentioning
confidence: 99%